Elective cesarean section v/s emergency cesarean section in primigravidae at term - Laqa, Sarwat; Lone, Samra Kashif; Begum, Saeeda; Rahman, Sana (Medical Journal of South Punjab, 2023)
Objective: To compare maternal and neonatal outcomes between elective cesarean section (ECS) and emergency cesarean section (EmCS) in primigravidae at term.Methodology: Comparative cross-sectional study was conducted in department of Obstetrics & Gynecology, Memon Medical Institute Karachi, Pakistan from January 2022 to December 2022. A total of 150 primigravidae at term (?37 weeks gestation) undergoing cesarean section were included. Patients were divided into two groups: elective cesarean section (n=75) and emergency cesarean section (n=75). Data regarding maternal demographics, indications for cesarean section, intraoperative and postoperative complications, and neonatal outcomes were recorded.Results: The mean age of patients was 26.3 ± 4.2 years. Maternal complications such as postpartum hemorrhage (18.7% vs 8.0%), wound infection (14.7% vs 5.3%), and need for blood transfusion (20.0% vs 9.3%) were significantly higher in the emergency cesarean section group compared to the elective group (p